Digital displacement: The psychological impact of virtual learning environments on international students’ sense of belonging and identity formation - Al-Jaloudi, Diya Ahmad; Al-Taleb, Jehan Abdullah; Kareem Al-Jaloudi, Ahmad Abedel; Al-Tamimi, Mustafa Qasem (Journal of International Students, 2026)
International student enrolment represents a significant portion of modern higher education; however, entirely online programs may foster distinct forms of alienation. This study presents the notion of digital displacement, defined as the alienation experienced when cultural engagement, social recognition, and academic involvement are predominantly facilitated by virtual learning environments. It investigates the correlations between digital displacement and international students’ sense of belonging, identity formation, and psychological distress. A total of 121 international students enrolled in online degree programs completed assessments of digital displacement, belonging, identity, and distress, subsequently responding to open-ended enquiries regarding their online experiences. Quantitative findings indicated that students experiencing diminished digital displacement (enhanced social presence and connectivity online) also exhibited markedly elevated feelings of belonging and reduced levels of anxiety, depression, and stress. Digital displacement (β = –0.45, p < .001) was the strongest unique predictor of overall psychological distress in a regression model. Identity difficulties (β = 0.36, p < .001) came in second. Belonging was not a unique predictor when modelled with displacement and identity, even though it was protective at the bivariate level. A mediation analysis showed that belonging did not have an indirect effect on distress through displacement. Qualitative responses reflected these trends: students articulated feelings of isolation and “invisibility” online, challenges in articulating their cultural identity, and fatigue from navigating technology, highlighting the necessity for enhanced community-building and support within virtual programs. These findings provide a new way to think about online alienation and give useful advice for culturally sensitive online advising, virtual campus design, and psychosocial support services that will help international students connect with each other and feel better in cyberspace.